2015
DOI: 10.1590/1414-431x20144337
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive dosimetry for cutaneous radiation syndrome

Abstract: According to the International Atomic Energy Agency (IAEA), a relatively significant number of radiological accidents have occurred in recent years mainly because of the practices referred to as potentially high-risk activities, such as radiotherapy, large irradiators and industrial radiography, especially in gammagraphy assays. In some instances, severe injuries have occurred in exposed persons due to high radiation doses. In industrial radiography, 80 cases involving a total of 120 radiation workers, 110 mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In that incident, involving arc welding quality control, an Ir-192 source was found outside its storage container. A worker held the source in his hand then transferred it to his pocket, with the total time of exposure estimated at 40 min (1,900 Gy skin surface exposure) (40). The patient was transferred to the burn treatment department of Percy Hospital, and a new dosimetry-guided surgical approach was used to examine the pathology of the lesion after removal (41).…”
Section: Session 1: Skin Injuries From Radiation and Other Clinical Cmentioning
confidence: 99%
“…In that incident, involving arc welding quality control, an Ir-192 source was found outside its storage container. A worker held the source in his hand then transferred it to his pocket, with the total time of exposure estimated at 40 min (1,900 Gy skin surface exposure) (40). The patient was transferred to the burn treatment department of Percy Hospital, and a new dosimetry-guided surgical approach was used to examine the pathology of the lesion after removal (41).…”
Section: Session 1: Skin Injuries From Radiation and Other Clinical Cmentioning
confidence: 99%
“…According to the IAEA and United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR), up to 2011 there were 80 radiological accidents in industrial radiography, involving 120 radiation workers and 110 members of the public, with 12 deaths. Brazilian data, from 1985 to 2018, includes five serious radiological accidents that affected seven radiation workers and 19 members of the public; the radiation workers developed cutaneous radiation syndrome to the hands and fingers [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 10 years, several methods and techniques have been used to perform reconstructive dosimetry and consequently the evaluation of doses in cases of radiological accidents [9]. These methods include: luminescent properties of electronic components of mobile phones [11,12]; numerical dosimetry using the Monte Carlo N Particle (MCNP) computational code [13,14]; electronic paramagnetic resonance [15,16]; the computational code Simulation of External Source Accident with Medical Images based on the anthropomorphic voxel phantom associated with MCNP [14]; Brazilian visual Monte Carlo Dose Calculation (VMC) [8,17,18], among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, industrial radiography accidents are one of the most frequently reported accidents among all reported cases in nuclear-related industries [2]. According to Lima et al [3], a total of 80 industrial radiography accidents involving 120 workers and 110 members of the public, including 12 deaths, were recorded globally between 1896 and 2014.…”
Section: Introductionmentioning
confidence: 99%